Urban setting, environmental context and thermal comfort in Puno city - Estrada Cahuapaza, Yeny Roxana (2017)
This research project entitled aims to determine levels of urban thermal comfort of the City of Puno by the influence of urban settings, open spaces and their environmental context, using the analytical, deductive, and hypothetical method. As a first step we have the description of the environment and climate in the City of Puno, in a second stage we study spaces according to the geomorphology in which the city of Puno is located by analyzing each of these morphologically urban zones, by the HM ratio aspect, sky SVF view factor and selected orientation in each road using the technique of direct observation, and simulation in the ECOTECT program, obtaining in this also the incidence of radiation road surfaces. At open public spaces it was also analyzed by its shape and vegetation. In a third step the analysis of urban thermal comfort was conducted in each area and selected through technical survey routes using the Fanger scale, which establishes a valuation index called "Vote Middle Dear" (PMV), which is results obtained as the low and varying levels of urban thermal comfort presented in the city of Puno.